Tratamento de efluentes líquidos de unidades produtoras de farinha de mandioca - Lima, Roberto Albuquerque (2010)
Cassava (Manihot esculenta) is the third most important crop in the basic food of the Brazilian population. The production of cassava flour generates an effluent, called manipueira , containing high organic matter and cyanide. The objective of this study was to investigate the removal of chemical oxygen demand (COD), turbidity and cyanide from cassava wastewater by physical-chemical and biological treatments. In the physicalchemical treatment by coagulation-flocculation, three full factorial designs were carried out to investigate the factors: pH, tannin concentration and the flocculation polymer (Polipan) concentration on the response variables: COD, turbidity and cyanide. The maximum efficiency for COD removal was 91 % at pH 8.0 in the presence of tannin 1.0 mL/L and Polipan 0.030 ppm. The highest removal of turbidity (75 %) was determined at pH 8 and tannin 0.8 mL/L in the absence of Polipan to reduce the costs of treatment. Under these conditions, the maximum removal of cyanide was 12 %. In the aerobic biological treatment for 48 h, the maximum efficiencies for COD reduction of 88 % and for turbidity reduction of 69 % were determined in the presence of the microbial consortium 20 % v/v, ammonium chloride 5 6 % and at pH 8.0. For the treatments, physical-chemical and biological, the results show that pH 8 is a key factor for removal of organic compounds and cyanide from cassava wastewater. The treatments of the manipueira by coagulation-flocculation and by microbial consortium decrease the pollution of this effluent before being launched in the water resources